Quilting : 20 mindful makes to reconnect head, heart & hands - Beaven, Elli (Conscious living publication., 2021)
Making is mindfulness made practical, and quilting is a renowned and rewarding craft. In Mindful Makes: Quiltingmaker Elli Beavenreveals the meditative nature of the quilting process and its empowering skillset for creating, mending and mindfulness. Drawing on the traditions of hand quilting, Elli has created 20 modern makes, ranging from simple coasters, bags and cushions to quilts and curtains. She shares the basic techniques of quilting and shows how these can be adapted and developed for different projects, as well as mending and repurposing. Clean photography, contemporary illustration and heart-affirming text are neatly sewn together to celebrate handwork and the act of crafting for a sustainable future. Packed with inspiring ideas and practical guidance, Mindful Makes: Quilting gives you the skills to get started with this fulfilling craft, and shows how the quilting process and the satisfaction of creating our own unique makes can benefit our wellbeing.